Curing cryptoglandular anal fistulas—Is it possible without surgery? - Chuang Wu; Zubing Mei; Zhenyi Wang (Heliyon)
Background: Empirical reviews suggested that cryptoglandular anal fistulas require surgical resolution. However, some reports have indicated the possibility of nonsurgical and conservative treatment, which is discussed in this review. Methods: This review explores the potential of nonsurgical approaches for curing anal fistulas through bacterial inhibition and immunomodulation. The longstanding cryptoglandular theory has been a subject of controversy, prompting the reevaluation of conventional surgical interventions for anal fistulas. The review was conducted through database searches, including Medline, EMBASE, PubMed, and the Cochrane Library. Results: Emerging evidence suggests that targeting the anaerobic environments present in anal fistulas and perianal abscesses and eradicating bacteria and their by-products may be critical for successful treatment. Immunomodulatory strategies show promise as a potential avenue for the nonsurgical management of anal fistulas. Conclusions: Ongoing developments in pharmacological research offer opportunities for alternative treatment options, shedding light on the prospects of noninvasive anal fistula management.